Structure, Conformational Landscape and UV-Induced Selective Rotamerization of 2-Aminoacetanilide - Brito, Anna Luiza B.; Justino, Licinia L. G.; Çatıkkaş, Berna; Lopes, Susy; ILDIZ, GÜLCE ÖĞRÜÇ; Fausto, Rui (Elsevier Science SA, 2023)
The molecular structure, conformational space and UV-induced rotamerization and decarbonylation of 2-aminoacetanilide (2AA) were investigated by matrix isolation infrared spectroscopy and quantum chemical electronic structure calculations. The compound was isolated in a cryogenic (15 K) argon matrix, and four conformers were spectroscopically identified: two trans-amide (O--C-N-H dihedral - 180 degrees) conformers (trans-I and trans-II), and two higher-energy cis-amide (O--C-N-H dihedral - 0 degrees) conformers (cis-I and cis-II). These four conformers were found to be present in the as-deposited matrix of 2AA in a population ratio matching well that predicted by the calculations for the gas-phase equilibrium at the temperature of the vapor of the compound before deposition (60 degrees C = 333.15 K). The calculations predicted also the existence of an additional higherenergy trans-amide conformer (trans-III) which was not observed experimentally. In situ broadband UV irradiation (lambda > 235 nm) of the matrix-isolated compound was found to induce selective conversion of conformer trans-I into conformer trans-II, in a few minutes (55 % after 2 min. of irradiation; 70 % after 10 min.), while the populations of the cis-amide conformers did not change. Prolonged UV irradiation was found to result in decomposition of the compound, leading to generation of carbon monoxide and 2-amine-N-methylaniline. The infrared spectra of the experimentally relevant conformers of 2AA were interpreted and assigned with help of normal coordinate analysis, and the different behavior of the conformers of 2AA upon UV-irradiation of the argon matrix was explained with help of time-dependent DFT (TD-DFT) calculations.
Keywords: 2-Aminoacetanilide; Matrix Isolation; Low Temperature Infrared Spectra; Dft(B3lyp)/6–311++g(d.p) Calculations; UV-induced Conformational Isomerization; Decarbonylatio